Liver function and serum amylase alterations following laparoscopic and open cholecystectomy and its significance - Singh, Krishna K.; Singh, Dhirendra P.; Chandra, Abhijeet; Alam, Mahboob; Agrawal, Priyanka (International Surgery Journal, 2019)
Background: Gall stone disease is the commonest gastro intestinal disease requiring surgical intervention, laparoscopic cholecystectomy (LC) which has replaced open cholecystectomy (OC). LC has more advantages over OC but has few drawback such as CO2 pneumoperitoneum leading to altered liver functions. The study was done with the aim to compare liver function tests in patients undergoing LC & OC and to compare these values in two groups preoperatively and postoperatively at 24 hrs, 48 hrs, 72 hrs. Methods: A total of 151 patients were admitted with cholelithiasis, out of which 72 patients underwent surgery between January 2018 to January 2019. Patients were selected by block randomization method into 2 groups containing 28 in each (Group 1- OC and Group 2- LC). SGPT, SGOT, LDH, TB, DB, IB, ALP and S. amylase were studied pre-operatively and at intervals of 24 hrs, 48 hrs, 72 hrs postoperatively. Comparison was made between both groups. Results: Pre and postoperatively stage, the level of LFT in Group 1 and Group 2 were similar except IB, which was significantly high in Group 1. At 24 hrs the difference in TB, DB, SGPT and S. amylase were statistically significant (p<0.05) between the groups. At 48 hrs difference between Group 1 and Group 2 in TB, DB, SGOT and SGPT were statistically significant (p<0.05). At 72 hrs difference between Group 1 and Group 2 in only SGPT was statistically significant (p<0.05). Conclusions: Cholecystectomy (OC and LC) lead to transient but reversible significant hepatic enzymes alterations. These alterations are self limited and return to reference values within 10 days of operation. The cause of alteration might be liver tractions, electrocoagulation’s and manipulation of duct.